MANIFESTASI ORAL TERKAIT IMMUNE RECONSTITUTION INFLAMMATORY SYNDROME PADA HUMAN IMMUNODEFICIENCY VIRUS/ ACQUIRED IMMUNODEFICIENCY SYNDROME - Embun Manja Sari; Wahyu Hidayat (Universitas Baiturrahmah, 2022)
Introduction: Treatment for Human Immunodeficiency Virus (HIV) infections using antiretroviral (ARV) resulting in varying stage response in the oral cavity. Some studies showed good responses but can also lead to Immune Reconstitution Inflammatory Syndrome (IRIS). IRIS is widely known as a complication of ARV therapy. Oral lesions in HIV / AIDS patients that emerge after taking ARV therapy can be categorized as IRIS cases. This systemic review aims to observe oral manifestations associated with IRIS. Review: Systematic review is carried out by the PRISMA method. The inclusion criteria are clinical trial articles collected from electronic searches, including full text through the PubMed portal, Research Gate, and Google Scholar using keywords: HIV / AIDS, IRIS, and oral manifestations which were published from 2011 to December 2019. A total of 6 articles were identified. The results showed that oral lesions in HIV/ AIDS related to IRIS are Kaposi Sarcoma 29.2%, OHL 16.9%, oral candidiasis 11.5%, and RAS 5.6%. The incidence of IRIS was around 10-27% in HIV / AIDS patients who have started ARV therapy. The incidence of IRIS is higher in prevalence in patients starting ARV therapy with low CD4 counts. Conclusion: Oral manifestations associated with IRIS in most HIV /AIDS patients are Kaposi's Sarcoma, OHL, Oral candidiasis, and SAR